Pengaruh Model Pembelajaran Proyek Terhadap Perkembangan Kemampuan Bersosialisasi Pada Anak Usia 5-6 Tahun - Salsabilla Madinah; Undang Rosidin; Nopiana Nopiana (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
One of the important models for improving the socialization skills of early childhood is the project learning model. The purpose of this study was to determine the effect of the project learning model on the development of socialization skills in children at Kindergarten 'Aisyiyah 3 Kampung Baru, Bandar Lampung, aged 5-6 years. This study is a quantitative study with an experimental method with a one-group pretest-posttest design. The population was 50 children with a sample of 25 children using purposive sampling. Data collection techniques used documentation and observation. The results showed that the application of the project learning model increased the average score from the pretest (20.44) to the posttest (32.44). With an N-Gain score of 0.584, it is in the moderate category. The project learning model has an influence of 56.3% on improving children's socialization skills, according to the results of a simple linear regression test, with an R Square value of 0.563. These results support the idea that the application of the project learning model has a significant effect on improving the social aspects of early childhood.